Evaluation of Subsurface Damage in Concrete Deck Joints Using Impact Echo Method - Larry Rickard; Wonchang Choi (Advances in Materials Science and Engineering)
Many factors can affect the overall performance and longevity of highway bridges, including the integrity of their deck joints. This study focuses on the evaluation of subsurface damage in deteriorated concrete deck joints, which includes the delamination and corrosion of the reinforcement. Impact echo and surface wave technology, mainly a portable seismic property analyzer (PSPA), were employed to evaluate the structural deficiency of concrete joints. Laboratory tests of core samples were conducted to verify the nondestructive test results. The primary advantage of the PSPA as a bridge assessment tool lies in its ability to assess the concrete’s modulus and to detect subsurface defects at a particular point simultaneously.